Advancing Simulation-Based Orthopaedic Surgical Skills Training: An Analysis of the Challenges to Implementation. (2nd September 2019) - Atesok, Kivanc; Hurwitz, Shepard; Anderson, Donald D.; Satava, Richard; Thomas, Geb W.; Tufescu, Ted; Heffernan, Michael J.; Papavassiliou, Efstathios; Theiss, Steven; Marsh, J. Lawrence
Abstract : Simulation-based surgical skills training is recognized as a valuable method to improve trainees' performance and broadly perceived as essential for the establishment of a comprehensive curriculum in surgical education. However, there needs to be improvement in several areas for meaningful integration of simulation into surgical education. The purpose of this focused review is to summarize the obstacles to a comprehensive integration of simulation-based surgical skills training into surgical education and board certification and suggest potential solutions for those obstacles. First and foremost, validated simulators need to be rigorously assessed to ensure their feasibility and cost-effectiveness. All simulation-based courses should include clear objectives and outcome measures (with metrics) for the skills to be practiced by trainees. Furthermore, these courses should address a wide range of issues, including assessment of trainees' problem-solving and decision-making abilities and remediation of poor performance. Finally, which simulation-based surgical skills courses will become a standard part of the curriculum across training programs and which will be of value in board certification should be precisely defined. Sufficient progress in these areas will prevent excessive development of training and assessment tools with duplicative effort and large variability in quality.